Modifications in the Surface of Titanium Substrate and the Incorporation of an Essential Oil for Biomaterial Application - Ferreira, Carolina Cruz; de Sousa, Lucíola Lucena; Barboza, Carla Sérgio; Marques, Rodrigo Fernando Costa [UNESP]; Mariano, Neide Aparecida (Springer Nature, 2022)
Metallic prostheses are the most used for the partial or total recovery of damaged organs and tissues, with titanium being the most applied material. Aiming to enhance the device to be implanted, the application of polymeric and ceramic coatings has been studied. The use of polycaprolactone (PCL) has shown promising characteristics, given its biodegradability, and the addition of hydroxyapatite (HA) has favored osseointegration. Nevertheless, complications related to infectious processes are recurrent to surgical procedures. In this context, the present study proposes the manufacture of a functional hybrid material for prosthetic application. As a strategy to minimize postsurgical bacterial contamination, this work proposes the incorporation of Melaleuca alternifolia essential oil (TTO) as a natural bactericide, in polycaprolactone and hydroxyapatite coatings in a titanium substrate. The samples were characterized to demonstrate that the coatings were performed on the whole surface of the titanium and that the incorporation of the essential oil did not alter the morphology of the polymeric film. The surface morphological evaluation performed after the corrosion assays in simulated body fluid indicated there was PCL degradation, being more intense for the samples containing HA, deriving from the alteration in the polymeric coating hydrophilicity combined with the bioceramic and the increase in surface porosity. Simultaneously to the process of polymeric layer degradation, it is suggested that there will be a release of the TTO incorporated in PCL and the formation of overlapping apatitic layers. Therefore, the results demonstrated that the proposed coatings may contribute to biocompatibility and the osseointegrative process, indicating the potentiality for application in orthopedic medical devices.
Keywords: hydroxyapatite; Melaleuca alternifolia; polycaprolactone; titanium